RESPON MASYARAKAT PENCARI KEPITING BAKAU (SUKU ASMAT DAN MAPPI) DENGAN MENGGUNAKAN BOXCRAB DI PESISIR LAMPU SATU KABUPATEN MERAUKE - Siti Masiyah; Riza Fachrizal (Musamus Devotion Journal, 2019)
Beside having high mangrove potential, Merauke Regency also has very high mangrove crab, this can be seen from the annual report of the Fisheries Service, the mangrove crab is the superior product of Merauke Regency. The method used is descriptive. The population is 17 crab seekers and the village officials in Samkai Village, Lampu Satu, Merauke Regency. Data collection was through interview and documentation techniques. Analysis of data was through tabulations and percentages, as a basis for interpretation and description in making reports. The community of crab seekers in Merauke Regency in Lampu Satu coastal Merauke District is a livelihood mostly carried out by the Asmat and Mappi tribes. The community of crab seekers was found in Lampu Satu, which was firstly 17 people and became 3 people, only carried out by women from the Mappi tribe. The results of the questionnaire survey of 17 respondents, the fishing gear used by the community are still very simple besides using hands directly also using ancu, machetes and traps. The fishing gear used in one catch is between 2-5 fishing gear. Presentation results is that 90% of the community do not know about the boxcrab before the socialization, it is easy to understand the technique of making boxcrab, the food of mangrove crabs and the techniques of feeding. The survey result is that the 60% of community were not interested in enlarging mangrove crabs using the boxcrab. Key words: the community, seeker, crab, boxcrab, the tribe of Asmat and Mappi